Farm Land Rental: Study of Takhrij and Syarah Hadith on Agrotechnology - Muhamad Ziyad; Kifah Gibraltar Bey Fananie; Neli Alawiah; Tuti Garnasih (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the hadith of the Prophet Muhammad regarding the lease of land or agricultural land. This research method is quantitative through takhrij and syarah hadith approaches with agrotechnology analysis. The result and discussion of this is the prohibition of leasing agricultural land in the time of the Prophet Muhammad. but there are still many in modern times who still rent land or agricultural land. The conclusion of this research is takhrij and syarah hadith of the Prophet Muhammad regarding the lease of agricultural land with argotechnology analysis that can cause disputes between tenants of agricultural land and those who rent agricultural land.